Perancangan Model Sistem Informasi Penunjang Operasional pada Lembaga Bimbingan Belajar - Oktavia, Tanty (Bina Nusantara University, 2013)
Tutoring institution is an organization which focuses in education. The objective of this institution is improving the quality of learning of all students to achieve the desired target. The operational activities of this institution consist of registration, scheduling, evaluation, and administration supporters. It will be less effective if the processes are done manually. Therefore, many institutions are starting to restructure the model of information systems to support the company’s operations. This study describes about designing an information system model using object oriented approach based on the methodology introduced by Satzinger, where each phase is represented by using UML diagrams. The result achieved in this research is to produce a general model of information systems in supporting the operations of a tutoring institution. Designing an information system that is compatible with business processes can maximize the company's operations to run efficiently and effectively so as provides a competitive advantage from its competitors.